Middleware Based Model of Heterogeneous Systems for SCADA Distributed Applications - UNGUREAN, I.; PENTIUC, S. G.; GAITAN, V. G.; GAITAN, N. C.; DODIU, E. (Advances in Electrical and Computer Engineering, 2010)
Infrastructure underlying the distributed information systems is heterogeneous and very complex. Middleware allows the development of distributed information systems, without knowing the functioning details of an infrastructure, by its abstracting. An essential issue on designing such systems is represented by choosing the middleware technologies. An architectural model of a SCADA system based on middleware is proposed in this paper. This system is formed of servers that centralize data and clients, which receive information from a server, thus allowing the chart displaying of such information. All these components own a specific functionality and can exchange information, by means of a middleware bus. A middleware bus signifies a software bus, where more middleware technologies can coexist.